Pertanggungjawaban Notaris dalam Kasus Akta yang Dinyatakan Batal Demi Hukum - Utoyo, Marsudi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
Notaries have an important role as public officials authorized to create authentic deeds that have perfect evidentiary power. However, in practice, the deed made by a notary can be declared null and void by law if it does not meet the formal or material requirements according to the legislation. This study aims to analyze the forms of notary accountability in such cases, both from legal, ethical, and civil responsibility aspects. Hasil penelitian menunjukkan bahwa notaris dapat dimintai pertanggungjawaban dalam tiga dimensi utama: (1) pertanggungjawaban hukum, dalam bentuk sanksi pidana, perdata, atau administratif jika terbukti melanggar hukum; (2) pertanggungjawaban etika, melalui Dewan Kehormatan Notaris dalam kasus pelanggaran kode etik profesi; dan (3) pertanggungjawaban perdata, dalam bentuk kewajiban untuk mengganti kerugian kepada pihak yang dirugikan. This conclusion emphasizes the importance of professionalism, diligence, and compliance with the law by notaries to prevent the annulment of deeds by law and to maintain the integrity of the notarial profession in the eyes of the public.